Brand Equity, Offering Equity, and Relationship Equity (BOR) Influence toward Customer Loyalty of Lombok Paradise Pearl Product - Dini Trijayati; Jerry Heikal (International Journal of Social Service and Research (IJSSR), 2023)
The research was conducted with the aim of proving the influence of Brand Equity, Offering Equity, and Relationship Equity on Customer Loyalty for Mutiara Lombok Paradise Products, with a sample of 104 samples. The method in this paper is non-probability sampling and the samples are randomly selected by means of stratified random sampling. The primary data used in this research is primary funds. This study has a hypothesis, namely Brand Equity, Offering Equity, and Relationship Equity on Customer Loyalty for Mutiara Lombok Paradise Products. Data was collected with the help of a questionnaire with a differential semantic scale for the dependent variable and a binary scale for the independent variable. The research results were analyzed using the SPSS (Statisical Program for Social Science) method. The study found that (1) Brand Equity has a significant effect on customer loyalty (2) Offering Equity has a significant effect on customer loyalty (3) Relationship equity has a significant effect on customer loyalty (4) Brand equity, Offering Equity, and Relationship equity both have an effect significant effect on customer loyalty.